Virtual visits: Reminiscence in residential aged care with digital mapping technologies. (4th February 2021) - Webber, Sarah; Baker, Steven; Waycott, Jenny
Abstract: Objective: Digital technologies can support reminiscence and lifestyle enrichment in residential aged care. This study explores potential benefits and risks of virtual visits using digital maps, tablet computers and virtual reality technologies. Methods: Reminiscence sessions were conducted with metropolitan aged care facility residents (n = 7), using digital mapping applications to 'visit' places of personal significance. Residents and family members (n = 4) were interviewed. Results: Some older adults found virtual visits valuable and all reminisced in various ways about personal, family and social experiences. Family members felt that virtual visits would be enriching for loved ones and that they supported sharing of life stories. Our results also highlight that VR usability improvements are needed to better suit older people. Conclusion: Virtual visits could offer valuable opportunities for positive reminiscence for some older adults in residential aged care. Digital technologies need to provide better support for older users and people who assist them.